Development of Powtoon-Based Audiovisual Media in English Language Subjects for Class VIII SMP - Rambe, Desy Khairani; Eldarni, Eldarni (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research was motivated by the lack of variation in the use of learning media in the form of technology at SMPN 5 Panyabungan. This media development aims to develop audiovisual media in English class VIII SMP subjects in order to produce a media that is valid and practical to use. The type of research and model used in this research is Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. . The validity test of the product developed was carried out by 2 (two) lecturers from the Department of Curriculum and Educational Technology and 1 (one) class VIII teacher at SMPN 5 Panyabungan. Product trials or practicalities were carried out on 28 class VIII SMP students. The data collection instruments used are documentation, assessment formats and questionnaire sheets. The validation results from the validator assessment of media expert I and media expert II were categorized as